Intimidation Against Press Freedom in Indonesia During Demonstrations Against the TNI Law - Usfunan, Maria Angelin; Usfunan, Yohanes (IJBLE Scientific Publications Community Inc., 2025)
Freedom of the press stands as one of the fundamental pillars of democracy and human rights, serving as an essential mechanism for public oversight, transparency, and the dissemination of information. Although constitutionally guaranteed by the 1945 Constitution of Indonesia and reinforced through Law No. 40 of 1999 concerning the Press, the practice of press freedom in Indonesia continues to face substantial challenges, including intimidation, violence, and criminalization of journalists. This study aims to identify the various forms of intimidation and violence faced by journalists, analyze their implications for freedom of expression and human rights, and propose recommendations for strengthening legal protection mechanisms for the press in Indonesia. Employing a normative legal research method with statutory, conceptual, analytical, and case approaches, the study examines the relationship between legal norms and their practical implementation. Case studies, such as the assaults on journalists Wildan Pratama and Rama Indra during coverage of the protests against the revision of the Indonesian National Armed Forces Law (UU TNI), reveal the inadequacy of legal protection and the persistence of human rights violations in the journalistic field. The findings demonstrate that violence against journalists not only infringes upon individual rights but also undermines democratic governance and social justice. Therefore, this research emphasizes the necessity of reinforcing legal frameworks, implementing national journalist safety protocols, enhancing legal literacy among law enforcement, and fostering collaboration between the government, the Press Council, and civil society to create a secure, independent, and ethical media environment in Indonesia.